Strategic value contribution role of HR - Naznin, Humaira; Hussain, Md Ashfaq (© 2016 Sage Publications India Pvt. Ltd, 2018)
This article was published in the Management Development Institute [© 2016 Sage Publications India Pvt. Ltd.] and the definite version is available at: https://doi.org/10.1177/0972262916637274 The Article's website is at: http://journals.sagepub.com/doi/10.1177/0972262916637274